Usefulness of Signal-averaged ECG, Short-term Heart Rate Variability, QT Interval and T Loop Criteria in Predicting 2 Years Lethal Outcome after Myocardial Infarction - Urbonavičienė, G.; Gargasas, L.; Aržanauskienė, R.; Bertašienė, Z.; Tamošiūnaitė, M.; Blužaitė, I. (Elektronika ir Elektrotechnika, 2006)
For evaluation of prognostic power usefulness of parameters of signal averaged ECG, short-term heart rate variability (HRV), QT interval and T loop morphology 116 patients with myocardial infarction were enrolled to a follow up study. During follow up of 2 years 16 patients died. A signal-averaged ECG was obtained 5 to 7 days after hospitalization. QT interval variables were measured automatically by means of appropriate computer software. HRV characteristics were assessed from rhythmograms. Vectorcardiographic 3D T loop was projected onto a vertical plane and parameters of T loop morphology were evaluated. Using logistic regression there was established the complex of informative parameters for lethal outcome. Hereby we could define a “high risk” group of patients with αQRS-T>96, QRSd>109, CV<3.1, LF>111 ms2, LVEF≤40%. The proposed model is simple and could be applied in the clinical practice to evaluate risk of death, to screen patients with unfavourable prognosis and to choose the best treatment for these patients. Ill.1, bibl. 7 (in English; summaries in English, Russian and Lithuanian).